Білоруси на теренах Степової України: особливості культурної адаптації та збереження ідентичності (за польовими матеріалами 2017-2018 років) - Боса, Л. (Народна творчість та етнологія, 2018)
У статті йдеться про особливості «життєвого світу» нащадків білоруських переселенців зі Смоленщини на Півдні України. Через родинні перекази, особисті документи відтворено форми і способи адаптації мігрантів на новому місці та сучасні стратегії збереження культурної ідентичності. Крім того, здійснено спробу розкрити специфіку етнокультурної взаємодії і самоорганізації населення на цих теренах. Наголошено, що традиційні вміння білорусів-ткачів не лише були важливими в процесі адаптації спільноти, але й стали внеском у нематеріальну культурну спадщину краю в сучасних умовах. The article is dedicated to the life-world peculiarities of the descendants of the Byelorussian migrants from the Smolensk region to the South of Ukraine in the early 19th century. Some forms and methods of adaptation of the settlers in a new place and modern strategies of cultural identity preservation are reproduced through the family legends and personal documents. Also, an attempt is made to reveal the specific character of ethno-cultural interaction on these territories and the possibilities of the population's self-organization. It is emphasized that the traditional skills of Byelorussian weavers have been important not only in the process of community adaptation but also have become a contribution to the immaterial cultural heritage of the region in modern conditions.